Harry Edwards at the podium delivering a speech. - Spartan Daily:::Creator::::::::::::
Harry Edwards stands at a podium and speaks to an audience. Two other African American men are seated behind Edwards. This event likely relates to campus tension over racial discrimination at San Jose State College.